A motivação de estudantes adolescentes de espanhol de um Centro de Estudos de Línguas - Andrade, Flavia Hatsumi Izumida (2016)
This master's research aims to 1) analyze and 2) configure the motivation by teenage students of spanish in a Language Study Center (CEL) in a learning process. We understand motivation as a complex and dynamic system, according to Dörnyei and Ushioda (2012) and Larsen-Freeman and Cameron (2008). The system is composed of different factors (systems or subsystems) that interact constantly. From this interaction, the stability of the complex system suffers shocks, causing changes because of time and / or interactions between the components themselves. Besides that, another goal of this research was to identify the motivators affordances (PAIVA, 2009) that became responsible por student’s staying in the course. Thus, data from twelve participants, obtained through the three data collection instruments (questionnaire, learning diary and semi-structured interviews), qualitatively analyzed through interpretive baseline analysis, the final step of the analysis was made a cutout in the data and we began to deepen the analysis of data from six of the participants. The research is characterized as action research, because the researcher was also teaching the participants. From the reports of the participants, first a) identified the initial motivation of each one to learn Spanish to later b) find affordances (PAIVA, 2009) that may have altered its initial condition of the motivational system. It is understood affordance as opportunities to connect with the foreign language (LE), which in addition to emerge in language, generate changes in the motivational complex systems of the participants. The results show that participants mostly did not have initial motivation to learn Spanish, but in contact with affordance, their motivational complex systems had been increasing. The most recurrent affordance for motivation were identified: interaction / group training; activities in the classroom and teacher performance. This may seem to be the main affordance responsible for the change of the initial student’s motivation. The conclusion is that teacher performance was felt by the participants of the research as subjective and also because of hers metodolical and didactical choises.